Shaykh al-Islām’s Dream Is Coming True: From Evkaf Bank to Vakif Participation Bank, Establishing a Bank with a Cash Waqf - Hatice Kübra Kahya (Darulfunun Ilahiyat)
Vakif Participation Bank was established in 2015 as a joint stock company with capital from the mazbūt awqaf under the full management and representation of the T.R Directorate General of Foundations and the Bayezid II, Mahmut I, Mahmut II, and Murat Pasha Foundations. Establishing a bank with a cash waqf [foundation] was essentially the dream of the sheikh al-Islam and the Awqaf Minister of the Second Constitutional Era, Mustafa Hayri Efendi. In 1914, he achieved this dream to a certain extent by getting Parliament to pass Evkaf Bankası Kanunu (Evkaf Bank Law). However, the outbreak of World War I impeded the de facto establishment of this bank. His dream partially came true with the establishment of Vakiflar Bank in 1954, then more fully with the establishment of Vakif Participation Bank in 2015 through the amount received from the treasury in exchange for the waqf shares in Vakiflar Bank. This article will tell the tales of these three different banks from three different worlds that aimed to establish a bank with a cash waqf by revolving around the legal institutions of cash waqf, usury, and istibdal [exchange].